2014
DOI: 10.3389/fsurg.2014.00018
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Automated Follicle Volume Measurements in IVF/ICSI

Abstract: Background/Aims: The objective of this literature study is to investigate the place of recent software technology sonography-based automated volume count (SonoAVC) for the automatic measurement of follicular volumes in IVF/ICSI. Its advantages and disadvantages and potential future developments are evaluated.Methods: A total of 74 articles were read via a PubMed literature study. The literature study included 53 articles, 32 of which for the systematic review.Results: The SonoAVC software shows excellent accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Obtaining an AFC is already associated with costs for the ultrasound machine and ultrasound technician; increased costs associated with three-dimensional ultrasound may be prohibitive. Furthermore, three-dimensional imaging has not been shown to improve clinical results, and, as with standard twodimensional imaging, image quality can vary depending on the patient (Vandekerckhove et al, 2014).…”
Section: Disadvantages Disadvantagesmentioning
confidence: 97%
See 2 more Smart Citations
“…Obtaining an AFC is already associated with costs for the ultrasound machine and ultrasound technician; increased costs associated with three-dimensional ultrasound may be prohibitive. Furthermore, three-dimensional imaging has not been shown to improve clinical results, and, as with standard twodimensional imaging, image quality can vary depending on the patient (Vandekerckhove et al, 2014).…”
Section: Disadvantages Disadvantagesmentioning
confidence: 97%
“…Poor-quality images may affect the reliability of AFC, particularly in women with ovarian cysts, fibroids, or scars from previous surgeries. The choice of ultrasound machine also has an impact on image quality Vandekerckhove et al, 2014). In addition, AFC tends to overestimate the true number of FSH-sensitive follicles and oocytes retrieved, perhaps because it also includes non-viable atretic follicles of the same size.…”
Section: Disadvantages Disadvantagesmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the individualized color code for each hypoechoic area eliminates the possibility of measuring the same follicle more than once. The program also shortens the time needed for follicular assessment, thereby improving the clinical work flow …”
mentioning
confidence: 99%
“…The program also shortens the time needed for follicular assessment, thereby improving the clinical work flow. [7][8][9][10][11][12][13] Thus far, only 2 prospective studies have addressed the impact of the new automated follicular diameter measurement on fertility outcomes. 14,15 Raine-Fenning et al 14 showed no significant difference between manual and automated follicle tracking in terms of the number of oocytes retrieved, number of mature oocytes, or pregnancy rate.…”
mentioning
confidence: 99%